Phylogenetic Analysis of the Thylakoid ATP/ADP Carrier Reveals New Insights into Its Function Restricted to Green Plants - Spetea, Cornelia; Pfeil, Bernard E.; Schoefs, Benoit (Frontiers in Plant Science, 2012)
ATP is the common energy currency of cellular metabolism in all living organisms. Most of them synthesize ATP in the cytosol or on the mitochondrial inner membrane, whereas land plants, algae, and cyanobacteria also produce it on the thylakoid membrane during the light-dependent reactions of photosynthesis. From the site of synthesis, ATP is transported to the site of utilization via intracellular membrane transporters. One major type of ATP transporters is represented by the mitochondrial ADP/ATP carrier family. Here we review a recently characterized member, namely the thylakoid ATP/ADP carrier from Arabidopsis thaliana (AtTAAC). Thus far, no orthologs of this carrier have been characterized in other organisms, although similar sequences can be recognized in many sequenced genomes. Protein Sequence database searches and phylogenetic analyses indicate the absence of TAAC in cyanobacteria and its appearance early in the evolution of photosynthetic eukaryotes. The TAAC clade is composed of carriers found in land plants and some green algae, but no proteins from other photosynthetic taxa, such as red algae, brown algae, and diatoms. This implies that TAAC-like sequences arose only once before the divergence of green algae and land plants. Based on these findings, it is proposed that TAAC may have evolved in response to the need of a new activity in higher photosynthetic eukaryotes. This activity may provide the energy to drive reactions during biogenesis and turnover of photosynthetic complexes, which are heterogeneously distributed in a thylakoid membrane system composed of appressed and non-appressed regions.